Intervention of social anxiety on children: Group counseling using miracle technique and scaling questions - Anis Lud Fiana (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2022)
Purpose - This research aims to test miracle tests and scaling questions to reduce social anxiety in a foster child.Method - This research applied an experimental method with One Group Pretest-Posttest design involving 7 foster children in SOS Children's Village Semarang as the subject of the research.Result - The result of this research shows that group counseling using the miracle technique and scaling questions is found effective to reduce social anxiety in foster children.Implication – These techniques could help the counselee to think in the present and the future. The use of miracle questions is perhaps on how the client's feeling or how the client would think. Miracle questions technique could be combined with scaling questions that could be done in helping the counselee to determine their objective, measure their progress, or to determine priority to take action..Originality - This research is presented the scaling questions technique focuses on the solution as well as the use of scaling questions on the individual's experience experiencing changes.***Tujuan - Penelitian ini bertujuan untuk menguji miracle test dan skala pertanyaan untuk menurunkan kecemasan sosial pada anak asuh.Metode - Penelitian ini menggunakan metode eksperimen dengan desain One Group Pretest-Posttest yang melibatkan tujuh anak asuh di SOS Children's Village Semarang sebagai subjek penelitian.Hasil - Hasil dari penelitian ini menunjukkan bahwa konseling kelompok dengan menggunakan teknik miracle dan scaling questions terbukti efektif untuk menurunkan kecemasan sosial pada anak asuh.Implikasi - Teknik-teknik ini dapat membantu konseli untuk berpikir di masa sekarang dan masa depan. Penggunaan pertanyaan keajaiban mungkin dapat digunakan untuk mengetahui bagaimana perasaan klien atau bagaimana klien berpikir. Teknik pertanyaan ajaib dapat dikombinasikan dengan pertanyaan penskalaan yang dapat dilakukan untuk membantu konseli menentukan tujuan, mengukur kemajuan, atau menentukan prioritas untuk mengambil tindakan.Orisinalitas - Penelitian ini menyajikan teknik scaling questions yang berfokus pada solusi serta penggunaan scaling questions pada pengalaman individu yang mengalami perubahan.